The oscillating pulse arrival time as a physiological explanation regarding the difference between ECG- and Photoplethysmogram-derived heart rate variability parameters. (January 2023) - Ajtay, Bella Eszter; Béres, Szabolcs; Hejjel, László
Highlights: The difference in current and preceding PAT explains the discrepancy of RRI and PPI. The PAT oscillates and is likely coupled to respiration. HRV and PRV measures inherently differ, due to differences between two consecutive PATs. The RP% of PAT oscillation is minimal at ½ amplitude of the PPG and maximal at base point. Momentary PAT and the steepness of PPG change inversely, resulting in compensation. Abstract: Background and Objective: ECG-based heart rate variability (HRV), and more recently, optical pulse rate variability (PRV) analysis used in wearables are non-invasive tools of neurocardiac investigation. Pulse arrival time (PAT) is derived from their simultaneous recording. We examined the beat-to-beat PAT in greater detail, while analyzed the PRV to HRV relationship. Methods: We acquired 300sec ECG, photoplethysmogram (PPG), and respiratory-signals from 35 young, healthy volunteers while in a supine position including different breathing patterns. PAT at eight reference points on the PPG-side was assessed by the mean, relative precision (RP%) and spectral analysis. PRV and HRV parameters were compared by relative accuracy error (RAE) and the Bland-Altman-Ratio (BAR). Results: PAT showed the minimum RP% at the 1/2-amplitude point whereas RP% reached the maximum at the base point; its observed fine oscillation was associated to breathing as confirmed through spectral analysis. The instantaneous slope of PPG rise is inversely proportional to the corresponding PAT. RAE and BAR showed excellent agreement in 15 of 16 analysis at time-domain, mostly excellent or moderate on frequency-domain and nonlinear analysis. The inherent difference between HRV and PRV is formally due to the difference among two consecutive PATs. Conclusion and Significance: The present study supported the interchangeability of HRV- and PRV-analysis. Our formalistic explanation linking successive PAT-pairs and the inborn difference between HRV and PRV may bear further implications in selecting the appropriate fiducial points, approximating PRV to HRV measures, and in creating innovative neurocardiac parameters or complex PPG models/simulators.